Associating plasma aldosterone concentration with the prevalence of MAFLD in hypertensive patients: insights from a large-scale cross-sectional study - Shen, Di; Cai, Xintian; Hu, Junli; Song, Shuaiwei; Zhu, Qing; Ma, Huimin; Zhang, Yingying; Ma, Rui; Zhou, Pan; Yang, Wenbo; Hong, Jing; Zhang, Delian; et al. (Frontiers in Endocrinology, 2024)
Objective To explore the link between plasma aldosterone concentration (PAC) and the prevalence of metabolic dysfunction-related fatty liver disease (MAFLD) in hypertensive patients. Methods We analyzed data from 41,131 hospitalized patients from January 1, 2014, to December 31, 2023. Multivariate logistic regression models tested associations, with threshold, subgroup, and sensitivity analyses conducted to validate findings. Results For each 5-unit increase in PAC, the risk of MAFLD rose by 1.57 times, consistent even in the fully adjusted model. The odds ratios for the Q2, Q3, and Q4 groups compared to Q1 were 1.21, 2.12, and 3.14, respectively. A threshold effect was observed at 14 ng/dL, with subgroup and sensitivity analyses supporting these results. Conclusions This study reveals a significant positive association between elevated PAC levels and the prevalence of MAFLD in hypertensive patients. These findings underscore the imperative for further large-scale, prospective studies to validate and expand upon this correlation.